2010
DOI: 10.1007/s00423-010-0715-1
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open appendectomy—quality of life 7 years after surgery

Abstract: Patients after laparoscopic appendectomy show a higher degree of satisfaction with their body and their scar than patients after open appendectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…This is equivalent to other retrospective quality-of-life studies reporting follow-up percentages between 37 and 52% after 2.5 to 7 years of follow-up [2, 42-44]. Baseline characteristics did not significantly differ between R and NR suggesting that the R group reflects the whole study population.…”
Section: Discussionmentioning
confidence: 48%
“…This is equivalent to other retrospective quality-of-life studies reporting follow-up percentages between 37 and 52% after 2.5 to 7 years of follow-up [2, 42-44]. Baseline characteristics did not significantly differ between R and NR suggesting that the R group reflects the whole study population.…”
Section: Discussionmentioning
confidence: 48%
“…Many studies have reported the benefits of the laparoscopic approach over OA, including decreased morbidity, cost-effectiveness and length of hospital stay [16,17]. …”
Section: Discussionmentioning
confidence: 99%
“…However, it also conflicts with previous studies comparing LA and OA in terms of quality of life in both the short-term and the long-term in which better quality of life has been associated with LA. [18][19][20] Preference for the laparoscopic approach over the open approach in uncomplicated appendicitis is still justified because of the important role of laparoscopic appendectomy in surgical training and patient preference for minimally invasive surgery.…”
Section: Discussionmentioning
confidence: 99%